1997
DOI: 10.1063/1.593358
|View full text |Cite
|
Sign up to set email alerts
|

The structure, slip systems, and microhardness of C60 crystals

Abstract: The structure and microplasticity of high-purity fullerite C60 have been investigated comprehensively. The crystalline structure, lattice parameters, and phase transitions have been studied by x-ray diffractometry in the temperature range 30–293 K. It is found that the temperature corresponding to the orientational order–disorder phase transition is Tc=260 K. A considerable number of regions with stacking faults discovered in the samples leads to blurring of the fcc→sc phase transition in the temperature inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Its effectiveness was demonstrated previously in studies of single crystals of C 60 fullerite (Ref. 14) of the same small size as the C 70 crystals. This method is distinguished not only by its simplicity.…”
Section: Samples Of C 70 Fullerite and Experimental Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…Its effectiveness was demonstrated previously in studies of single crystals of C 60 fullerite (Ref. 14) of the same small size as the C 70 crystals. This method is distinguished not only by its simplicity.…”
Section: Samples Of C 70 Fullerite and Experimental Methodsmentioning
confidence: 76%
“…8; at room temperature H V % 170 MPa in C 60 fullerite. 14 In the transition to high-temperature phase severe cracking of the surface, its overturn, and deviation of the indented plane from the normal of indentation were observed. As a result, at T > 350 K indentations became less and less clear, often they were not symmetrical due to the incline of the surface, and severe cracking around the indentation was observed.…”
Section: Temperature Dependence Of Microhardness Of C 70 Single Crmentioning
confidence: 98%
“…1. This is probably related to the onset of orientation freezing of the rotation of Co molecules visible at ambient pressure at T0 = 150 K. The effect of this freezing was observed in bulk C60 [10][11][12] and C60 thin films [13,14].…”
Section: Resultsmentioning
confidence: 97%
“…Investigations performed by several teams of researchers (see [8] and the references ibid.) have revealed that macro-and microplastic deformation of fullerite C 60 at room and at moderately low temperatures is determined by the glide of dislocations in the {111}á ñ 110 slip system; the system is kept efficient even after the fcc-sc transition.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in the previous papers [5][6][7][8], the temperature dependence of microhardness of pure C 60 single crystals displays a step-like anomaly, the position of which is correlated with the temperature T c 260 K of the fcc-sc phase transition. It is known [9,10] that intercalation of an impurity into the C 60 lattice results, as a rule, in a decrease of T c and a broadening of the phase transition temperature range.…”
Section: Introductionmentioning
confidence: 96%